FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MEROKOK PADA REMAJA USIA 15-19 TAHUN DI KUTA SELATAN - SURBAKTI, IYOS ALFRANTA; SUSILAWATI, MADE; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 12 No 4 (2023), 2023)
Adolescence is a period of change in emotional, physical, interests and behavior patterns. Teenagers begin to leave childish attitudes and behavior and begin to show the ability to behave maturely. This smoking behavior can cause various negative impacts on adolescents both in terms of health, economics, social and psychological. This study aims to analysis what factors cause adolescents to smoke. The method used in this research is exploratory factor analysis. Based on the results of factor analysis, four factors were obtained that influenced smoking behavior among adolescents in South Kuta, namely psychological factors, advertising factors, knowledge factors, and family environment factors. These four factors are able to explain the factors that influence smoking behavior in adolescents in South Kuta by 64.667%.